Cooccurrence of Postural Orthostatic Tachycardia Syndrome with Two Different Clinical Entities. (19th June 2016) - Oztunc, Funda; Ugan Atik, Sezen; Dedeoglu, Reyhan; Erbek Alp, Firuze; Gokalp, Selman
Abstract : Postural orthostatic tachycardia syndrome (POTS) is an abnormal heart rate response to a positional change. Several potential mechanisms for pathophysiology of POTS are defined. This syndrome can coexist with different clinical situations. In our report, the first case was a 13-year-old female who has been followed up for diagnosis of homocystinuria. She was admitted to our outpatient clinic with complaints of dizziness after suddenly moving from supine to upright position and chest pain after exercise. Tilt table test was performed to evaluate dizziness. According to the tilt table test the patient was diagnosed with POTS. The second case was a 17-year-old female who had been evaluated in different centers with the complaints of fainting, bruising, redness, and swelling on the hands and feet after moving from supine position to upright position during the last 4 years. Postural orthostatic tachycardia syndrome was diagnosed by tilt table test and ivabradine was started. Herein, we aimed to point out the cooccurrence of different clinical entities and POTS.